Bone marrow stem cell therapy partially ameliorates pathological consequences in livers of mice expressing mutant human α1‐antitrypsin. Issue 4 (25th February 2017) - Baligar, Prakash; Kochat, Veena; Arindkar, Shailendra K.; Equbal, Zaffar; Mukherjee, Snehashish; Patel, Swati; Nagarajan, Perumal; Mohanty, Sujata; Teckman, Jeffrey H.; Mukhopadhyay, Asok
Abstract : Alpha‐1‐antitrypsin (AAT) deficiency (AATD) is a genetic disease, caused by mutation of the AAT gene. Accumulation of mutated AAT protein aggregates in hepatocytes leads to endoplasmic reticulum stress, resulting in impairment of liver functions and, in some cases, hepatocellular carcinoma, whereas decline of AAT levels in sera is responsible for pulmonary emphysema. In advanced liver disease, the only option for treatment is liver transplantation, whereas AAT replacement therapy is therapeutic for emphysema. Given that hepatocytes are the primary affected cells in AATD, we investigated whether transplantation of bone marrow (BM)‐derived stem cells in transgenic mice expressing human AATZ (the Z variant of AAT) confers any competitive advantages compared to host cells that could lead to pathological improvement. Mouse BM progenitors and human mesenchymal stem cells (MSCs) appeared to contribute in replacement of 40% and 13% host hepatocytes, respectively. Transplantation of cells resulted in decline of globule‐containing hepatocytes, improvement in proliferation of globule‐devoid hepatocytes from the host‐derived hepatocytes, and apparently, donor‐derived cells. Further analyses revealed that transplantation partially improves liver pathology as reflected by inflammatory response, fibrosis, and apoptotic death of hepatocytes. Cell therapy was also found to improve liver glycogen storage and sera glucose level in mice expressing human AATZ mice. These overall improvements in liver pathology were not restricted to transplantation of mouse BM cells. Preliminary results also showed that following transplantation of human BM‐derived MSCs, globule‐containing hepatocytes declined and donor‐derived cells expressed human AAT protein. Conclusion : These results suggest that BM stem cell transplantation may be a promising therapy for AATD‐related liver disease. (Hepatology 2017;65:1319‐1335).